2000
DOI: 10.1046/j.1365-2281.2000.00224.x
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric measurements of peripheral oedema in clinical conditions

Abstract: Water-displacement volumetry can be used for quantifying the volume of the leg. However, not much is known about its application in patients with peripheral oedema of cardiopulmonary origin. We measured the reproducibility of a water-displacement apparatus with a solid object and in ten non-oedematous clinical patients (group A). The day-to-day variability of the leg volume was assessed in the same group. The diurnal variability was assessed in ten patients with persisting peripheral oedema (group B). The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
1
6

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 7 publications
4
52
1
6
Order By: Relevance
“…5,7,12,13 Our data indicate that an obturator improves time efficiency during foot and ankle volumetry with no negative effects on the high observed reliability. In fact, the high Pearson's value showed that the obturator had a consistent and predictable effect on measurements.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…5,7,12,13 Our data indicate that an obturator improves time efficiency during foot and ankle volumetry with no negative effects on the high observed reliability. In fact, the high Pearson's value showed that the obturator had a consistent and predictable effect on measurements.…”
Section: Discussionmentioning
confidence: 52%
“…An obturator is a device that can be placed within a volumeter to prevent water turbulence or waves from reaching the overflow spout and prolonging the time taken for water to drain. It has been proposed that an obturator (a) increases the volume of displaced water and possibly increases the accuracy of the method, 13 (b) reduces water turbulence from leg movements, 5 and (c) decreases surface tension of the water, thereby improving accuracy. 12 None of these hypotheses has been evaluated, however, even in studies where an obturator was used to improve accuracy.…”
mentioning
confidence: 99%
“…18 Volumetric measurements commonly have been conducted to evaluate the amount of edema present in a limb. [19][20][21][22] However, volumetric and circumference measurements of the leg also have been conducted as a representation of muscle mass and function. 23,24 Athletes with greater volume measurements have been identified as having increased muscle power and strength.…”
mentioning
confidence: 99%
“…Exclusion criteria involve current assisted ambulation (eg, cane or crutches); inability to bear weight through the affected extremity immediately after injury with tenderness to palpation of the medial and lateral malleolar zones, styloid process of the 5 th metatarsal, and navicular [36]; positive anterior drawer or inversion stress maneuver suggesting ligamentous laxity [37-39]; volume of the affected limb greater than 10% of the unaffected limb per water displacement volumetry [40]; previous history of ligament or bony reconstructive surgery to the ankle and foot; concomitant injury to other lower extremity joints; and inability to comply with the treatment protocol.…”
Section: Methodsmentioning
confidence: 99%